Simulated and experimental verification of the microwave dual-band metamaterial perfect absorber based on square patch with a 450 diagonal slot structure. Issue 11 (24th July 2021) - Al-badri, Khalid Saeed Lateef; Abdulkarim, Yadgar I.; Alkurt, Fatih Özkan; Karaaslan, Muharrem
Abstract : In this paper, we designed a dual band metamaterial perfect absorber (MPA) for Ku band applications. The overall ultrathin layer of proposed absorber consists of square patch with 450 diagonal slot structure within a copper square patch which loaded on both sides of dielectric thickness 1.6 mm FR-4 substrate. The results show that designed MPA gives two absorption bands at 12.45 and 14.18 GHz and absorption rates are 99.73% and 99.87% respectively. The proposed dual-band absorber has a polarization sensitive characteristic, the absorption performance is almost changing with different polarization angles. Furthermore, resonance centres of two absorption bands can be adjusted by changing related parameters. The novelties of proposed structure are simple, easy fabricate, low cost, durable, suitable for real-time applications and long-term stability considering the fabrication technique and non-destructive measurement method. The dualband absorber can be used in practical applications such as bolometer, EM wave spatial filter and satellite communications.